Transmembrane helix connectivity in Orai1 controls two gates for calcium-dependent transcription - Frischauf, Irene; Litviňuková, Monika; Schober, Romana; Zayats, Vasilina; Svobodová, Barbora; Bonhenry, Daniel; Lunz, Victoria; Cappello, Sabrina; Tociu, Laura; Reha, David; Stallinger, Amrutha; Hochreiter, Anna; et al. (Science signaling, 2017)
The channel Orai1 requires Ca2+ store depletion in the endoplasmic reticulum and an interaction with the Ca2+ sensor STIM1 to mediate Ca2+ signaling. Alterations in Orai1-mediated Ca2+ influx have been linked to several pathological conditions including immunodeficiency, tubular myopathy, and cancer. We screened large-scale cancer genomics data sets for dysfunctional Orai1 mutants. Five of the identified Orai1 mutations resulted in constitutively active gating and transcriptional activation. Our analysis showed that certain Orai1 mutations were clustered in the transmembrane 2 helix surrounding the pore, which is a trigger site for Orai1 channel gating. Analysis of the constitutively open Orai1 mutant channels revealed two fundamental gates that enabled Ca2+ influx: Arginine side chains were displaced so they no longer blocked the pore, and a chain of water molecules formed in the hydrophobic pore region. Together, these results enabled us to identify a cluster of Orai1 mutations that trigger Ca2+ permeation associated with gene transcription and provide a gating mechanism for Orai1.
Keywords: buněčná membrána; Calcium; Ion Channel Gating; Drosophila melanogaster; nemoci svalů; HCT116 buňky; nádorové proteiny; Humans; gating iontového kanálu; Protein Structure, Secondary; Stromal Interaction Molecule 1; ORAI1 Protein; vápník; mutace; genomika; Patch-Clamp Techniques; lidé; HEK293 Cells; sekundární struktura proteinů; zvířata; metoda terčíkového zámku; protein STIM1; Arginine; simulace molekulární dynamiky; Muscular Diseases; Transcriptional Activation; aktivace transkripce; Molecular Dynamics Simulation; HEK293 buňky; Neoplasms; arginin; nádory; HCT116 Cells; Animals; Cell Membrane; Mutation; Neoplasm Proteins; Genomics; protein ORAI1